Semantic and Functional Poliphony of the French Verb devoir ‘must’. A Cross-Linguistic Study / La polyphonie sémantico–fonctionnelle du verbe français devoir. Etude interlangagière - Valiukienė, Vita (Kalbotyra, 2015)
The paper explores the variety of meanings of the French verb devoir ‘must’ in a cross-linguistic (French-Lithuanian) perspective. A survey of the literature published on the diachronic development and synchronic semantic dynamics of this verb in the French language is presented. The focus is on the concepts of deontic modality, epistemicity, and evidentiality categories in the French linguistics tradition. The model of modality offered by French linguists is discussed (lexical meaning → deontic modality → alethic modality → epistemicity) and the process of gramaticalization in language has been briefly touched upon. The data have been collected from French and Lithuanian original fiction books and their translations into Lithuanian and French. The findings of the pilot study carried out show that the verb French devoir ‘must’ is polysemous and multifunctional, which is mirrored in its Lithuanian translation correspondences. Very frequent translation correspondences of the deontic devoir ‘must’ into the Lithuanian language have been found to be verbs gauti ‘get to’, privalėti ‘must’, reikėti ‘need’, tekti ‘be gotten to’, turėti ‘have to’. On the contrary, among the translation correspondences of epistemic devoir ‘must’ in Lithuanian adverbial expressions of probability greičiausiai / tikriausiai / turbūt / veikiausiai ‘(most) probably’ have been most common. Further research based on a parallel French-Lithuanian corpus data analysis will test the validity of the hypotheses that there is a difference in the choice of adverbial and verb strategies in coding epistemic modality in French and Lithuanian. Abstract in French